Diagnostic Accuracy of Calretinin for Malignant Mesothelioma in Serous Effusions: a Meta-analysis - Li, Diandian (Sci Rep, 2015)
Numerous studies have investigated the utility of calretinin in differentiating malignant mesothelioma (MM) from metastatic carcinoma (MC) in serous effusions. However, the results remain controversial. The aim of this study is to determine the overall accuracy of calretinin in serous effusions for MM through a meta-analysis of published studies. Publications addressing the accuracy of calretinin in the diagnosis of MM were selected from the Medline (Ovid), PubMed, the Cochrane Library Database and the Web of Science. Data from selected studies were pooled to yield summary sensitivity, specificity, positive and negative likelihood ratio (LR), diagnostic odds ratio (DOR), and receiver operating characteristic (SROC) curve. Statistical analysis was performed by Meta-Disc 1.4 and STATA 12.0 softwares. 18 studies met the inclusion criteria and the summary estimating for calretinin in the diagnosis of MM were: sensitivity 0.91 (95%CI: 0.87–0.94), specificity 0.96 (95%CI: 0.95–0.96), positive likelihood ratio (PLR) 14.42 (95%CI: 7.92–26.26), negative likelihood ratio (NLR) 0.1 (95%CI: 0.05–0.2) and diagnostic odds ratio 163.03 (95%CI: 54.62–486.63). The SROC curve indicated that the maximum joint sensitivity and specificity (Q-value) was 0.92; the area under the curve was 0.97. Our findings suggest that calretinin may be a useful diagnostic tool for confirming MM in serous effusions.